Advantages of Dinar and Dirham and Profit Sharing System In Monetary Policy - Zakiyyah Ilma Ahmad; Mustofa Mustofa (Universitas Trunojoyo Madura, 2022)
The research gap as well as the novelty of this research in comparison to previous research is that it discusses the advantages of the profit-sharing system as a better monetary policy that may overcome the monetary crisis caused by the interest rates. This study analyzed the advantages of the dinar and dirham as well as the profit-sharing on monetary policy. This study proved that the dinar and dirham and the profit-sharing are solutions to the economic crisis.Under the qualitative approach, library research was carried out by collecting information related to the monetary crisis in 1998 and 2008 caused by currencies and interest rates. The advantages of the dinar and dirham, as well as profit-sharing, were analyzed. This study revealed that the monetary crisis greatly impacted the economy from 1997 to 1998 and in 2008, one of which was caused by the instability of exchange rates and interest rates. This study suggests that monetary policy should be reconsidered, as it was during the Prophet's time, by using dinar and dirham as fixed and stable mediums of exchange, as well as a profit-sharing system that avoids interest-rate speculation and takes advantage of dinar and dirham and the profit-sharing system.